2013
DOI: 10.4204/eptcs.112.12
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning about Strategies under Partial Observability and Fairness Constraints

Abstract: A number of extensions exist for Alternating-time Temporal Logic; some of these mix strategies and partial observability but, to the best of our knowledge, no work provides a unified framework for strategies, partial observability and fairness constraints. In this paper we propose ATLK^F_po, a logic mixing strategies under partial observability and epistemic properties of agents in a system with fairness constraints on states, and we provide a model checking algorithm for it

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The problem they solve is a bit different from AT L ir as, for the formula ⟪player⟫F win ∧ ⟪player⟫F lose to be true, the same uniform strategy must be winning for both formulas, while AT L ir allows different strategies to witness the satisfaction. Also, their idea is very similar to the first solution of Busard et al [9,11], shown to be highly ineffective compared to the partial approach [10].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The problem they solve is a bit different from AT L ir as, for the formula ⟪player⟫F win ∧ ⟪player⟫F lose to be true, the same uniform strategy must be winning for both formulas, while AT L ir allows different strategies to witness the satisfaction. Also, their idea is very similar to the first solution of Busard et al [9,11], shown to be highly ineffective compared to the partial approach [10].…”
Section: Resultsmentioning
confidence: 94%
“…These approaches can be improved with pre-filtering, a technique that reduces the number of strategies to consider [9,11]. If some move does not belong to a winning general strategy, then it cannot belong to a uniform winning one.…”
Section: Introductionmentioning
confidence: 99%
“…The formulas φ i j are called the guards of the knowledge-based program. 8 Intuitively, this program says to repeat forever the following operation: nondeterministically execute one of the actions a i j such that the corresponding guard φ i j is true. To ensure that it is always the case that at least one action enabled, we assume that φ i 1 ∨ .…”
Section: Reasoning About Knowledge-based Programsmentioning
confidence: 99%
“…(b) call S AT (Γ, E, Σ, (t, β), φ 1 ). 8. If φ = ∃x(φ 1 ), then existentially guess a global state (t, β), and universally A straightforward argument based on the semantics of the logic shows that the above correctly computes SAT.…”
Section: Corollarymentioning
confidence: 99%
“…When the fairness options are enabled all operators are evaluated on the set of fair paths as discussed in [9].…”
Section: Fairness For Atlkmentioning
confidence: 99%